Analysis of Factors That Influence Employee Performance of PT Bumimulia Indah Lestari Cilegon Banten - Suhartini; Ratu Dea Mada (Ilomata International Journal of Management, 2020)
This study aims to determine the factors that influence employee performance at PT. Bumimulia Indah Lestari Cilegon Banten. The independent variables Social security and work motivation are the factors that are analyzed partially and simultaneously on the Dependent Variable of Employee Performance at the company. The number of samples in this study was 70 employees is a saturated sample. The analysis technique in this research uses a validity test, reliability test, classic assumption test, multiple linear regression analysis, t-test, F test, and R2 test. The research method used is a descriptive quantitative method that is a measurement of object data by processing data using SPPS V.25.0 software. The results showed that (1) Social security variables partially did not have a positive and significant effect on the performance of the employees of PT Bumimulia Indah Lestari, as evidenced by the t-value of 1,458 < t-table 1,668 with a sig value of 0.150> 0.05. (2) Work Motivation Variable partially positive and significant effect on the performance of the employees of PT Bumimulia Indah Lestari, evidenced by t-value 2,375> t-table 1,668 with a sig value of 0.02 <0.05. (3) Social Security and Work Motivation Variables simultaneously have a positive and significant effect on Employee Performance of 19.6% s on the performance of employees of PT Bumimulia Indah Lestari, where the F-value is 8,189> F table 3.13 with a sig value of 0.001 < 0.05. Suggestions for PT Bumimulia Indah Lestari pay more attention to the timeliness of employees in carrying out their work so that the company's targets are met properly.